Barriers to scholarly publishing among library and information science researchers: International perspectives - Lund, Brady D.; Wang, Ting; Shamsi, Amrollah; Abdullahi, Jamilu; Awojobi, Esther Abosede; Borgohain, Dhruba Jyoti; Bueno de la Fuente, Gema; Huerta, Gilberto Parra; Isfandyari-Moghaddam, Alireza; Islam, Md. Anwarul; Khasseh, Ali Akbar; Lamba, Manika; et al. (Sage Publications Ltd, 2021)
The 21 authors of this study, 19 of whom are non-native English speakers, reflect on the barriers to publishing academic journal articles in top international journals. Each author responded to the same set of questions pertaining to educational (PhD) opportunities for emerging scholars, financial conditions for researchers, and challenges in publishing their work. Limited English language skills, lack of research funding, and different research topics were identified as the most significant barriers to publish in the journals. Recruiting volunteers or using electronic translations for accepted articles for journals, reducing software and subscription to academic journals costs, expanding journal scope, and providing guidance and collaboration across borders are possible measures to reduce the negative impact of the barriers.
Keywords: barriers; developing countries; research productivity; publishing; library and information science; international; language; hegemony; global south; journals